PERANAN MEDIA SOSIAL DALAM MENGEMBANGKAN SUATU BISNIS: LITERATURE REVIEW - Sankist Herdiyani; Cecep Safa'atul Barkah; Lina Auliana; Iwan Sukoco (Jurnal Administrasi Bisnis, 2022)
Nowadays, social media has become one of the important technologies that involved in human daily life including business. There are many benefits that entrepreneurs can get to develop their business by utilizing social media to communicate business. Thus, this research aims to determine the social media roles in developing business. This research used descriptive qualitative research method with Systematic Literature Review (SLR). The outcome of this research are social media has a role as a place for business development in marketing products through the marketing mix, increasing customer engagement of a business, increasing sales in the midst of covid-19 pandemic situations, and become a place for representing a business. Social media is also needed in advancing competition of local wisdom SMEs to support the Indonesian economy. So, social media is a way for entrepreneurs to develop their business.